Postharvest Losses, Food Safety and Value Chain of Fruit and Vegetables in Sri Lanka for the Fruit and Vegetables for Sustainable Healthy Diets Initiative - Hewajulige, I.G.N.; Somasiri H. P. P. S.; Liyanaarachchi, G. V. V.; Rajawardana, D. U.; Madage, S.S.K.; Jayasinghe, M. D. (International Food Policy Research Institute, 2022)
This report by FRESH initiative partner University of Sydney, with collaborator Industrial Technology Institute of Sri Lanka, is a characterization of the fruit and vegetable value chain in Sri Lanka. This report is a synthesis of a literature review on postharvest management, with special emphasis on loss assessments, research and innovation, of fresh fruits and vegetables; a literature review on food safety, with special emphasis on food microbiology, such as the testing of pesticide residues on fresh vegetables; and a series of target key stakeholder interviews. This report identifies evidence gaps and areas for intervention and collaboration with many actors along the fruit and vegetable value chain.